Effectiveness of Opioids-Adjuvant Analgesics Combinations for Pediatric Cancer Pain: A Systematic Review - Ulfa Filliana; Susi Ari Kristina; Bekti Meilani Nurcahya (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: The pediatric cancer was reported that they got worst pain and 40% weren’t managed well. The impact of untreated cancer pain is low quality of life and poor pain experienced. Therefore, it is important to know the best analgesic for improving the clinical outcome of pain.Objectives: This study aims to determine the effectiveness of using opioid combined with adjuvant analgesics based on WHO analgesic ladder in pediatric cancer pain.Methods: PubMed and Science Direct were searched for randomized controlled trials and retrospective studies by the keyword’s “opioid”, “adjuvant analgesic”, “pediatric”, “cancer” within 2014-2024. The primary outcome was using Faces Pain Scale, or visual analog scale (VAS), or numerical rating scale (NRS).Results: A result of 556 studies were reviewed. After further inspection of collected studies, only 5 studies achieved all inclusion criteria. The final studies consist of two prospective studies with randomized trial and three retrospective studies. Combination gabapentin or pregabalin as adjuvant analgesic with opioids was better reduced pain intensity and less adverse events than other combinations.Conclusion: This study supports the increased effectiveness of analgesic opioid combined with adjuvant analgesics, compared with single opioid, in the treatment of pediatric cancer pain. Further study inspires researchers to conduct studies using the randomized trial method and continue meta-analysis study especially in pediatric population and developing countries.